(3eQhL GdPgH heYGOf GdLhgQs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s ((3bGSe Hf CMeO GdVhQGfi s)
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO , heSJhLH GdKfGA hGdeLO s
(3BNQgG (B:s
(3hBNQ GdLRA GdKGfi HYfhGf (B" (3hef NWH GdMSf ai CjGeg (B" (3bhdg (B: (3dGjfaY faSkG EjeGfgG de Jcf CefJ ef bHd Ch cSHf ai ZjeGfgG NjQkG Je GdLRA GdKGfi ef cJGH s
(3GdfSNI HgG MhGTs
(3cJHJ GdLRA GdGKfi efg SfI (B1067 (3g` HYfGjI YeGO GdOjf jMji Hf eMeOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277s
Keywords: (3GdJGQjNs